IUPHAR ECR review: Cancer-related anorexia-cachexia in cancer patients: Pathophysiology and treatment - Iftekhar Hossain Chowdhury; Shamima Rahman; Yeasmin Jahan Afroze; Sharmeen Tania Shovah (Elsevier, 2024)
Cancer-related anorexia-cachexia (CRAC) comprises one of the most common syndromes of advanced cancer patients. The prevalence of CRAC increases from 50% to 80% before death. CRAC is associated not only with impaired quality of life in patients and family members but also with shorter survival. The management of CRAC is a great challenge in clinical practice. There are no definite practice guidelines yet for the prevention and treatment of CRAC. A multimodal strategy is the most effective way to treat anorexia-cachexia. Numerous medications have been suggested and used in clinical trials, while others are still being studied on experimental animals. These medications include branched-chain amino acids, eicosapentaenoic acid, thalidomide, cytokine inhibitors, steroids, antiserotoninergic medications, and appetite stimulants. The benefits of supportive care interventions and the advancement of exciting new pharmacological medicines for anorexia-cachexia are becoming more widely recognized. Health care professionals need to be aware of the psychosocial and biological effects of anorexia-cachexia, even though knowledge of the underlying molecular causes of the disorder has advanced significantly.